Saintifik Quizlet: Analisis model terhadap kemampuan berpikir kritis matematis - Nuraini, Silvia; Kadarisma, Gida (IKIP Siliwangi, 2026)
This study aims to determine whether learning through a scientific approach will improve students' mathematical critical thinking skills. Mixed method is the method used in this study, using Parallel Convegent Design. All eighth-grade students of SMP Negeri 21 Bandung city served as the population in this study. Two classes were randomly selected, where class VIII-A was the experimental class and class VIII-G was the control class. A mathematical critical thinking test was given, consisting of five questions aligned with the indicators according to these abilities. The t-test results showed a difference between the posttest scores of the experimental class and the control class, with a significance level of 0.000 <0.05, which means that the use of a scientific approach assisted by Quizlet helped improve students' critical thinking skills. In addition, the questionnaire showed a very positive response to this approach, especially regarding student activity, learning interest, and motivation. Thus, the use of a scientific approach with Quizlet can make students more active, interested, motivated, and better understand mathematical concepts.